Correction: Publisher Correction: Store-independent modulation of Ca2+ entry through Orai by Septin 7 - Bipan Kumar Deb (Nature Portfolio, 2018)
Nature Communications 7: Article number: 11751 (2016); Published 26 May 2016, Updated 18 July 2018 The original HTML version of this Article had an incorrect article number of ‘0’; it should have been ‘11751’. This has now been corrected in the HTML version of the Article. The PDF version was correct from the time of publication.